Level Of Psychological Resilience Of Nurses In The Multi-services Clinic In Rouissat - Maache,salma (University Of Eloued جامعة الوادي, 2024)
Abstract: The current study aims to identify the level of psychological resilience of nurses working in the multi-services clinic in Rouissat. It was conducted on a sample of 30 (male and female) nurses in order to achieve the study's objectives; we adopted the the Connor-Davidson Resilience Scale (20003) translated to Arabic by el kalali .As we followed the exploratory descriptive approach which is mostly convenient in such studies.. The results of the study found a high level of psychological resilience among sample members, with no statistically significant differences in sample members' scores according to the following variables: sex and years of experience
Keywords: psychological résilience?; nurses; multi-services clinic